Analisa Kritis Terhadap Kristologi Unitarianisme dari Perspektif Teologi Injili - Sulistyoadi, Didik (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2025)
Unitarianism is one of the teological teachings that deviates from the orthodoxy of the Christian faith, instilled by Arius in the 3rd century and later popularized by Francis David and several other theologians in the 16th century. This teaching spread to Indonesia under the name of Unitarian Christianity because of its emphasis on absolute monotheism and rejection of the divinity of Jesus. This teaching is easily accepted because of its rationalistic theological approach. However, fundamentally, Unitarianism contains weaknesses and dangers for its adherents. This research was conducted using a descriptive qualitative approach through literature review and found the most fundamental weaknesses of Unitarianism teachings from the perspectives of theological methodology, theological content, and theological implications.